Configuration of a production line based on stakeholder requirement (2017)
The industry has been growing exponentially through the years. Thanks to technology, great improvements have been made in the area of production processes, for example the automation of thereof, where some of these processes have come to function in complete independency from operators. The complexity of these processes and the development of different techniques are increasing due to competition and high demand from the clients. This study takes a different perspective towards the production line analysis, where the objective is to design a specific line of production according to the client requirements. The former starts with the characterization of the line from the previous design process to the implementation. In order to accomplish this, it is proposed to create a virtual library where it can be found machinery information, with its corresponding characteristics according to their real life performance. This in favor of creating an algorithm that manages to find the optimal functioning that the production line requires, at the same time it satisfies the clients restrictions...